Meningkatkan Kemampuan Literasi Anak Usia 5-6 Tahun di TK Aisyiyah Bustanul Athfal Minasaupa Melalui Permainan Modern Teka-Teki Silang - Anisa, Nurul; Latuconsina, Nur Khalisah; Patiung, Dahlia; Kustiah, Sri (Faculty of Tarbiyah and Teacher Training, 2026)
This community service activity aims to describe the implementation of a modern crossword puzzle game as a learning medium to stimulate the literacy skills of 5-6-year-old children at Aisyiyah Bustanul Athfal Minasaupa Kindergarten. The activity was implemented using a service learning approach, involving five 5-6-year-old children as participants. Data were collected through observation sheets covering indicators of logical thinking, problem-solving, pattern recognition, vocabulary comprehension, and patience. Data were then analyzed using descriptive statistics. The results showed that most children achieved the Very Well Developed (BSB) category for indicators of logical thinking, problem-solving, pattern recognition, and vocabulary comprehension, while all children demonstrated good development in the patience indicator. These findings indicate that modern crossword puzzles can be used as a learning medium to support the development of early childhood literacy skills through active and enjoyable learning activities.